ANALISIS IMPLEMENTASI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TaRL) PADA PEMBELAJARAN MATEMATIKA KELAS IV DI SEKOLAH DASAR - Octa Juliska, Landia; Yantoro; Noviyanti, Silvina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the planning, implementation, and evaluation of the Teaching at The Right Level (TaRL) approach in mathematics learning for grade IV at SD Negeri 34/I Teratai in the even semester of the 2024/2025 academic year. This study uses a qualitative research type with a phenomenological approach. The subjects of the study included teachers and students of grade IV A. Data were collected through interviews, observations, and documentation, then analyzed by data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation of techniques and sources. The results showed that the implementation of TaRL consisted of three stages: planning, implementation, and evaluation. At the planning stage, teachers analyzed Learning Outcomes (CP), compiled Learning Objectives (TP), and prepared teaching materials. At the implementation stage, students were grouped based on their abilities through diagnostic assessments and the learning process followed the syntax of Problem Based Learning (PBL). Evaluation involved reflecting on the effectiveness of the approach on student understanding, motivation, and engagement. In conclusion, the implementation of TaRL systematically increases the effectiveness of mathematics learning by adjusting teaching methods to student characteristics.